2004
DOI: 10.1289/ehp.6262
|View full text |Cite
|
Sign up to set email alerts
|

Prospective pregnancy study designs for assessing reproductive and developmental toxicants.

Abstract: The determinants of successful human reproduction and development may act as early as periconceptionally, underscoring the need to capture exposures during these critical windows when assessing potential toxicants. To identify such toxicants, couples must be studied longitudinally prior to conception without regard to a couple's ability to ascertain a clinically recognized pregnancy. We examined the utility and feasibility of prospective pregnancy study designs by conducting a systematic review of the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 68 publications
(102 reference statements)
1
67
1
Order By: Relevance
“…The increasing methodologic complexities that are associated with capturing exposures, including environmental mixtures, in the context of lifestyle and behavior across critical windows of human development argue for prospective epidemiologic studies whose utility and feasibility have been demonstrated. 121,122 Ideally, such studies would incorporate longitudinal biospecimen collection at timed intervals for the quantification of chemical mixtures and lifestyle exposures that may affect growth and development inclusive of pubertal milestones. Efforts to develop a suite of sensitive pubertal markers, rather than a sole marker, that are consistent with the manner in which humans are exposed are needed.…”
Section: Research Priorities and Future Directionsmentioning
confidence: 99%
“…The increasing methodologic complexities that are associated with capturing exposures, including environmental mixtures, in the context of lifestyle and behavior across critical windows of human development argue for prospective epidemiologic studies whose utility and feasibility have been demonstrated. 121,122 Ideally, such studies would incorporate longitudinal biospecimen collection at timed intervals for the quantification of chemical mixtures and lifestyle exposures that may affect growth and development inclusive of pubertal milestones. Efforts to develop a suite of sensitive pubertal markers, rather than a sole marker, that are consistent with the manner in which humans are exposed are needed.…”
Section: Research Priorities and Future Directionsmentioning
confidence: 99%
“…We are unaware of any research focusing on women or couples' behavioral intentions while attempting pregnancy with regard to preconception guidance. This may reflect a limited number of prospective pregnancy studies with preconception enrollment of women assessing lifestyle and behavioral influences on human reproduction and development (26). The best evidence we have detailing the effect of parental exposures on the conceptus and early embryo comes from these studies.…”
Section: Advising the Pregnancy Planning Couplementioning
confidence: 99%
“…Such studies recruit couples upon discontinuing contraception so they can be followed through a year of trying for pregnancy, with the male partner providing baseline and, possibly, additional semen samples. The rarity of such studies has been described (Buck Louis et al ., 2004) and is likely one explanation for our inability to develop methods for the sensitive and specific prediction of male fecundity and related impairments based upon semen analysis results. In fact, we are aware of only two previous prospective cohort studies that enrolled and followed couples to assess semen quality in relation to couple fecundity, as measured by TTP (Bonde et al ., 1988; Zinaman et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%